Application of a newly developed large‐scale conceptual hydrological model in simulating streamflow for credibility testing in data scarce condition. (15th September 2020) - Paul, Pranesh K.; Kumari, Babita; Gaur, Srishti; Mishra, Ashok; Panigrahy, Niranjan; Singh, Rajendra
Abstract: Regionalization approach is adopted to test the credibility of a newly developed, large‐scale, conceptual hydrological model, namely, satellite‐based hydrological model (SHM), under data‐scarce conditions. SHM has a modular structure. There are five modules: surface water module (SW), which uses natural resources conservation service‐curve number and Hargreaves equation; forest module (F), which uses water balance and subsurface dynamics; snow module (S), which uses temperature index and radiation‐temperature index algorithms; groundwater module, which considers contributions from SW, F, and S modules and uses water level variation process; and routing module, which uses modified spatial distributed direct hydrograph model. Four neighboring basins of varying size are selected to form the reference (Subarnarekha) and the test (Brahmani, Baitarani, and Kangsabati) basins. The similarity index and hierarchical agglomerative cluster analysis show that Brahmani is the most homogeneous basin with respect to the Subarnarekha basin. The model simulations are run at 1 km resolution. The values of statistical indices Nash‐Sutcliffe efficiency, coefficient of determination, and percent BIAS, are found to be 0.82%, 0.84%, and 13.99%, respectively, during calibration (1993–1999; 1993 as a warm‐up period), and 0.61%, 0.63%, and 14.13%, respectively, during validation (2000–2004) at Jenapur gauging station of the Brahmani river basin. Subsequently, the calibrated parameters are transferred in the model setup of the Subarnarekha basin for simulating streamflow over a randomly chosen period 1998–2000. The results, obtained with both Brahmani and Subarnarekha parameters, confirm that the model performs well with the regionalized parameters, and is suitable for hydrologically homogeneous ungauged basins. The results show that the newly developed model may be used for the water balance simulations in ungauged or scantily gauged basins, leading to the development of water resources plans for better utilization of this vital resource. The results from the sensitivity analysis and uncertainty analysis show that the nonsensitive parameters have a negligible impact on the model results. Further study, however, may be needed to evaluate the model performance and to establish its universal credibility. Recommendations for Water Resource Managers and The Scientific Community 1. This successful testing of the newly developed hydrological model implies that it may be a useful tool for water resources assessment in data‐scarce conditions. 2. The encouraging results support the further application of the model for data‐scarce basins in different parts of India and the world. 3. This study, for the first time, applies a tool namely "cluster 3.0" (generally used in biotechnology) for hierarchical agglomerative cluster analysis to perform homogeneity test. Any modeler and policymakers may use the tool for homogeneity test of a basin with respect to a reference basin without learning the mathematical theory, in details. 4. The results of parametric sensitivity analysis would help the future modelers in applying this model by providing ideas of the value ranges of model parameters.